Transformasi Sistem Pendidikan Pesantren (Studi Perubahan Model Pesantren di Pesantren Bustanul Ulum Bulugading Bangsalsari Jember: Transformation of the Islamic Boarding School Education System (A Study of Model Change at Bustanul Ulum Islamic Boarding School, Bulugading Bangsalsari, Jember) - Nuruddin Nuruddin (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2014)
This research tries to analyze the transformation of the Islamic boarding school education system (a study of the Islamic boarding school model change at Bustanul Ulum Islamic Boarding School, Bulugading Bangsalsari, Jember). In analyzing this study, the researcher uses a descriptive qualitative approach with a repeating and continuing analysis technique between collecting and analyzing data, both during and after data collection. From the research results at Bustanul Ulum Islamic Boarding School, it was found that the transformation of Islamic boarding school education at Bustanul Ulum Islamic Boarding School, Bangsalsari Jember, began in 1970 by establishing an Islamic elementary school (Madrasah Ibtidaiyah), in 1978 an Islamic junior high school (Madrasah Tsanawiyyah) was built, while an Islamic senior high school (Madrasah Aliyah) was built in 1981, and the last one in 2010 was a vocational school (SMK). It was the process of transforming the pure salaf Islamic boarding school education system into a model of Islamic boarding school that includes formal institutions within it. The process of transforming the Islamic boarding school education system is driven by societal demands and needs, the era of development, and the Islamic students' need for life skills. Penelitian ini mencoba menganalisis transformasi sistem pendidikan pesantren (studi perubahan model pesantren di Pesantren Bustanul Ulum Bulugading Bangsalsari Jember). Dalam menganalisis penelitian ini, peneliti menggunakan pendekatan kualitatif deskriptif dengan teknik analisis berulang dan berkelanjutan antara pengumpulan dan analisis data, baik selama maupun setelah pengumpulan data. Hasil penelitian di Pesantren Bustanul Ulum menunjukkan bahwa transformasi pendidikan pesantren di Pesantren Bustanul Ulum Bangsalsari Jember dimulai pada tahun 1970 dengan mendirikan Madrasah Ibtidaiyah, pada tahun 1978 mendirikan Madrasah Tsanawiyyah, sedangkan Madrasah Aliyah didirikan pada tahun 1981, dan terakhir pada tahun 2010 mendirikan Sekolah Menengah Kejuruan (SMK). Ini adalah proses transformasi sistem pendidikan pesantren salaf murni menjadi model pesantren yang memiliki lembaga formal di dalamnya. Proses transformasi sistem pendidikan pesantren ini disebabkan oleh tuntutan dan kebutuhan masyarakat, perkembangan zaman, serta kebutuhan santri akan keterampilan hidup (Life Skill).